INDUCTION OF LONG-TERM T AND B CELL MEMORY IMMUNITY TO INFLUENZA A VIRUS (H5N1) IN PERSONS VACCINATED WITH LIVE INFLUENZA A VACCINE (H5N2) - I. V. Losev; S. A. Donina; G. D. Petukhova; D. A. Korenkov; M. K. Erofeeva; M. A. Stukova; L. G. Rudenko; A. N. Naykhin (Медицинская иммунология, 2017)
Over last years, a novel strategy for vaccination of people against potentially pandemic influenza A viruses is actively developed worldwide, i.e., a combined (prime-boost) vaccination. It provides  amplification (boosting) of immune response  for a vaccine  be means  of pre-vaccination (priming) with another vaccine.  We have first studied an issue of immunological consequences for people after priming  by live attenuated influenza H5N2 vaccine (LAIV), followed by a boost with inactivated influenza H5N1 vaccine (IIV) 1.5 years later. Unlike non-primed volunteers, the primed persons developed more rapid and high production of serum antibodies (of HAI-, MN-, ELISA-types) after a single vaccination with H5N1 IIV. That concerned induction of antibodies to the H5N1 vaccinal strain A, and other heterologous strains containing H5 haemagglutinin. In primed persons, the antibodies showed  higher  avidity as compared to non-primed individuals. Before inoculation with H5N1 IIV, the  IgG-antibody titers  to A virus (H5N1), and  the  levels of specific  CD4+  and  CD8+   memory T-cells proved  to be higher  in primed subjects  than  in non-primed persons.  The  boosting  effect  of H5N1 IIV did not correlate with HAI-and MN-based data on immunogenicity of priming  H5N2 live attenuated vaccine.  In general, the results obtained justify a new direction in applications of LAIVs for protection against potentially pandemic influenza virus A.